Optimizing Township Government Administration with Genetic Algorithms for a Green and Sustainable Rural Future - Rahman, Abdur; Hussain, Shaik Jakeer; Vani, M. Sandhya; Velu, C. M.; Rajkumar, N.; Srinivasa Rao, P. S. V.; Babu, G. Charles; Kanakaprabha, S. (Engineering, Technology & Applied Science Research, 2025)
India’s Sustainable Rural Development (SRD) policy is a pivotal step toward achieving equitable growth and strengthening rural governance structures. This study focuses on enhancing Gram Panchayat governance by proposing an Improved Genetic Algorithm (IGA)-based approach to streamline decision-making, optimize resource allocation, and foster participatory rural development. Household survey data collected in Karnataka (November 2022) inform the analysis, emphasizing best practices in rural governance and policy implementation. The findings highlight the critical role of local leadership, particularly village heads and Gram Panchayat Secretaries, in effectively overseeing SRD initiatives. Key recommendations include appointing village heads as SRD directors, deploying specialized officers to priority rural areas, and adopting standardized governance protocols. Between 2018 and 2022, performance metrics such as economic growth, citizen engagement, environmental sustainability, and rural wastewater management were evaluated. Results demonstrate that integrating IGA into rural development strategies significantly enhances resilience and sustainability outcomes. The proposed framework underscores the potential for improved funding mechanisms and administrative efficiency in addressing pressing rural challenges. This research provides valuable insights for policymakers, contributing to the advancement of India’s SRD goals and fostering a more inclusive and sustainable rural future.